2018
DOI: 10.2147/jpr.s153061
|View full text |Cite
|
Sign up to set email alerts
|

Clinimetric properties of the Nepali version of the Pain Catastrophizing Scale in individuals with chronic pain

Abstract: BackgroundPain catastrophizing is an exaggerated negative cognitive response related to pain. It is commonly assessed using the Pain Catastrophizing Scale (PCS). Translation and validation of the scale in a new language would facilitate cross-cultural comparisons of the role that pain catastrophizing plays in patient function.PurposeThe aim of this study was to translate and culturally adapt the PCS into Nepali (Nepali version of PCS [PCS-NP]) and evaluate its clinimetric properties.MethodsWe translated, cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 44 publications
10
26
0
1
Order By: Relevance
“…The test-retest reliability of the Hausa-PCS total score was highly adequate (ICC = 0.90) suggesting excellent reproducibility. Our value is higher than the original English version (ICC = 0.73) [23] and the range of 0.76-0.85 obtained by several language versions [33, 37, 39-43, 45, 47], consistent with the 0.90 obtained for the Afrikaans [35], Japanese [84], Nepali [77] and Xhosa [35] versions but slightly lower than the range of 0.92-0.97 obtained by other language versions [36,38,44,76]. However, for the Hausa-PCS subscales, the ICC was only adequate for the helplessness subscale (ICC = 0.89).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The test-retest reliability of the Hausa-PCS total score was highly adequate (ICC = 0.90) suggesting excellent reproducibility. Our value is higher than the original English version (ICC = 0.73) [23] and the range of 0.76-0.85 obtained by several language versions [33, 37, 39-43, 45, 47], consistent with the 0.90 obtained for the Afrikaans [35], Japanese [84], Nepali [77] and Xhosa [35] versions but slightly lower than the range of 0.92-0.97 obtained by other language versions [36,38,44,76]. However, for the Hausa-PCS subscales, the ICC was only adequate for the helplessness subscale (ICC = 0.89).…”
Section: Discussionsupporting
confidence: 89%
“…This nding is similar to the reports of many validations conducted in different samples of individuals with chronic pain [39,79,80,82]. On the contrary, other validations found the two-factor structure of the PCS to exhibit adequate model t [48,77]. In another vein, the Huijer et al [34] found the one-factor, two-factor (based on the authors' EFA), and Sullivan's original three-factor structures all exhibited adequate t to the Arabic population.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations